Long Lines Not So Practical in China while Small and Medium Sized Lines Favored - Chu, Shao-Ying; Sha, Run (Promet - Traffic&Transportation, 2003)
Maglev railroads have taken actual steps in China sincethe cooperation work between Germany and China, whichbrings more prospects to this technology. However, due to variousreasons, large-scaled long lines seem to be not so practicalat present in China, while the small and medium space scaledlines may be the initial alternatives with the booming ofthree super-metropolis groups in China, namely, the ZhujiangRiver Delta, the 'Grand Beijing' area and the Yangtze RiverDelta.